Type III restriction enzymes cleave DNA by long-range interaction between sites in both head-to-head and tail-to-tail inverted repeat - van Aelst, Kara (National Academy of Sciences, 2010)
Cleavage of viral DNA by the bacterial Type III Restriction-Modification enzymes requires the ATP-dependent long-range communication between a distant pair of DNA recognition sequences. The classical view is that Type III endonuclease activity is only activated by a pair of asymmetric sites in a specific head-to-head inverted repeat. Based on this assumption and due to the presence of helicase domains in Type III enzymes, various motor-driven DNA translocation models for communication have been suggested. Using both single-molecule and ensemble assays we demonstrate that Type III enzymes can also cleave DNA with sites in tail-to-tail repeat with high efficiency. The ability to distinguish both inverted repeat substrates from direct repeat substrates in a manner independent of DNA topology or accessory proteins can only be reconciled with an alternative sliding mode of communication.